2020
DOI: 10.1002/ctm2.262
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from human multipotent stromal cells protect against hearing loss after noise trauma in vivo

Abstract: The Effect of extracellular vesicles derived from human stromal cells on the inner ear has been investigated. The vesicles were characterized and tested in vitro in spiral ganglion neurons and in vivo in a mouse noise trauma model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 75 publications
(145 reference statements)
2
32
0
Order By: Relevance
“…The preparation of the batch that was used for injection contained 1.03 × 10 11 particles/ml with a diameter range of 110-130 nm as measured by nanoparticle tracking analysis (NTA, Model PMX110 from ParticleMetrix, Germany, Figure S Nanoparticle Tracking Analysis of UC-MSC-EVs). Surface profiling by multiplex flow cytometry demonstrated the presence of the tetraspanins CD9, CD63, CD81, as previously described (Warnecke et al, 2020) as well as MSC-EV markers CD29, CD44, CD49e and CD73 and revealed the absence of CD1/2/3/8/11c/14/19/20/24/25/31/40/45/56/69/86/133/142/209/326 and absence of the marker molecules HLA-ABC, HLA-DR, ROR1, SSEA-4 (Figure S Multiplex Marker Profiling of UC-MSC-EVs). Cryo-transmission electron microscopic imaging confirmed the presence of UC-MSC-EVs by visualization of double-layer lipid membranes around spherical objects (Figure 1b).…”
Section:  Preparation and Quality Control Of Human Umbilical Cord Mesenchymal Stromal Cell-derived Extracellular Vesicles (Uc-msc-evs)supporting
confidence: 56%
See 4 more Smart Citations
“…The preparation of the batch that was used for injection contained 1.03 × 10 11 particles/ml with a diameter range of 110-130 nm as measured by nanoparticle tracking analysis (NTA, Model PMX110 from ParticleMetrix, Germany, Figure S Nanoparticle Tracking Analysis of UC-MSC-EVs). Surface profiling by multiplex flow cytometry demonstrated the presence of the tetraspanins CD9, CD63, CD81, as previously described (Warnecke et al, 2020) as well as MSC-EV markers CD29, CD44, CD49e and CD73 and revealed the absence of CD1/2/3/8/11c/14/19/20/24/25/31/40/45/56/69/86/133/142/209/326 and absence of the marker molecules HLA-ABC, HLA-DR, ROR1, SSEA-4 (Figure S Multiplex Marker Profiling of UC-MSC-EVs). Cryo-transmission electron microscopic imaging confirmed the presence of UC-MSC-EVs by visualization of double-layer lipid membranes around spherical objects (Figure 1b).…”
Section:  Preparation and Quality Control Of Human Umbilical Cord Mesenchymal Stromal Cell-derived Extracellular Vesicles (Uc-msc-evs)supporting
confidence: 56%
“…Total protein amount of the used UC-MSC-EVs was 3.7 mg/ml. The biological activity of this particular clinicalgrade EV preparation was confirmed through in vitro and in vivo testing using inner ear cell culture and a noise trauma mouse model (Warnecke et al, 2020).…”
Section:  Preparation and Quality Control Of Human Umbilical Cord Mesenchymal Stromal Cell-derived Extracellular Vesicles (Uc-msc-evs)mentioning
confidence: 87%
See 3 more Smart Citations